Effect of maternal voice on physiological and behavioral measures in premature infants : a randomized controlled trial - Ghani, Nurul Amani Abd (2016)
Introduction Preterm infants lose significant contact with their mothers during prenatal development and nursed in hospital environment that exposed them to elevated stimulus from NICU environment. They are not only deprived from the protective properties of womb, they also remain in an enclosed incubator where touching and sensory stimulation are restricted which possibly a critical aspect for normal development, that is the mother’s voice Objective The aim of this study is to determine the effect of maternal voice vs NICU environmental sounds on physiological and behavioral measures in premature infants. Method This is a parallel randomized control trial conducted in NICU Hospital Sultanah Bahiyah, Alor Setar from June 2015 to Nov 2015. This study involved all premature infants with corrected gestational age 27-35 weeks who is already on full feeding and nursed in incubator. All subjects were randomized into two groups that are Intervention and Control. Their mother will be asked to sing appropriate lullabies that will be recorded for 10 minute duration. Infants were randomly assigned to one of two groups. Infants in the Control group received routine NICU nursing care. Infants in the Intervention group received routine NICU care as well as 10 minutes of exposure to their mothers recorded voice every day. for 14 days. Infants in the two groups were evaluated and observed for 30 minutes every day for 14 days. Heart rates, respiratory rates and oxygen saturation levels as displayed on the monitor were recorded every minute for 30 minutes. Behavioral score (BIIP) was measured at every 10 minute. Weight gain was measured every other day by a standardized digital weight scale. Infants were evaluated during 3 phases: 10 minute baseline, 10 minute intervention and 10 minute post intervention. Result A total of 138 patients completed the study. There was significant reduction of mean heart rate over time [F=5.071, p<0.05] and median respiratory rate over time (Z = -7.27, p < 0.01) in the intervention group. There was significant difference in median respiratory rate in intervention group (Z = -4.39, -4.23,-4.15, p <0.01) compared to control group. There was also significant increase of oxygen saturation in intervention group (Z = -2.14, -2.39, -2.56 p < 0.05). There was no significant difference in mean weight gain between intervention and control group [MD 0.30 (-1.9, 2.5), P>0.05]. There was no significant changes of Behavioral Indicator of Infant Pain profile (BIIP) with regard to time [Z = -0.31, -0.36, -0.65 P >0.05]. Conclusion This study showed that exposure to mother’s voice had positive effect on premature infant’s heart rate, respiratory rate and oxygen saturation while no changes on mean weight gain and behavioral score with no adverse reaction noted during intervention.